2019
DOI: 10.1155/2019/8657609
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antegrade Irrigation via Percutaneous Nephrostomy on Surgical Outcomes in Semirigid Ureteroscopy among Patients with Upper Ureteral Stones

Abstract: Objective. We aimed to investigate the role of antegrade irrigation via percutaneous nephrostomy on surgical outcomes in retrograde ureteroscopy in patients with upper ureter stones. Materials and Methods. In this retrospective study, we analyzed 134 patients who underwent retrograde semirigid ureteroscopy for upper ureter stones between August 2012 and December 2017. Patients were divided into two groups: retrograde irrigation group (conventional URS) and antegrade irrigation group (using percutaneous nephros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Georgescu et al (23) reported that prolongation of the operation time also increased the overall complication rate. In another study of 134 patients, it was reported that prolonged operation time increased UTI after semirigid URS (24) . Similarly, univariate analysis of our study indicated that the duration of URS was a significant risk factor for occurrence of UTI in the postoperative period.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Georgescu et al (23) reported that prolongation of the operation time also increased the overall complication rate. In another study of 134 patients, it was reported that prolonged operation time increased UTI after semirigid URS (24) . Similarly, univariate analysis of our study indicated that the duration of URS was a significant risk factor for occurrence of UTI in the postoperative period.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, success rate of URS in the general population was 88 percent. Patients with residual fragments represent an important risk group for postoperative UTI (12,24,26,27) . Castro et al (12) reported that the success rate increased to 94.2%, especially in distal ureteral stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is possible that the act of irrigation alone mechanically results in reduction of burden of disease. A study performed evaluating surgical complications due to stone retropulsion in upper ureteral stones revealed better outcomes when anterograde irrigation via percutaneous nephrostomy tube was delivered rather than retrograde irrigation via the bladder, suggesting that the irrigation alone may play a large role to decrease infective burden in this case [ 11 ]. Bladder irrigations with gentamicin were used successfully in preventing recurrence of cystitis in neurogenic bladder patients without systemic absorption [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, these devices may not be able to pass above the stone due to stone impaction or they may fail to completely secure the dilated ureter above the stone giving space for some fragments to escape between the device and the ureteric wall. Modifications for treating proximal ureteric stones have been reported in many clinical trials achieving superior outcomes and improving the SFR (Table 4 [10][11][12][13][14][15][16][17]).…”
Section: Discussionmentioning
confidence: 99%